Types of support received by Chilean novice homeroom teachers for their professional learning during induction - Moreno Díaz, Karina; Mauri Majós, Teresa; Colomina Álvarez, Rosa (Revista Complutense de Educación, 2025)
INTRODUCTION: Induction constitutes a key stage in the professional development of educators, presenting challenges for those undertaking the role of homeroom teacher. These professionals require substantial support to fulfill their responsibilities, learn their profession, and reduce turnover and attrition. This article aims to identify and characterize the support that novice homeroom teachers receive to promote their professional learning in the spaces where they participate in the school community to which they belong. METHOD: The research was conducted using an interpretative phenomenological approach. Semi-structured interviews were administered to 15 novice homeroom teachers from municipal, subsidized, and private educational institutions in Chile. The data were analyzed through thematic analysis and multiple correspondence analysis. RESULTS: Six types of support were identified, which materialize in formal activity spaces, integral to the organizational and operational structure of the educational center, and in non-formal activity spaces, which do not form part of this structure. In this latter type of activity space in where the types of support materialize most frequently. Additionally, it is in the professional activity space with specialists where a greater number of types of support are employed. DISCUSSION: In order to promote the professional learning of novice homeroom teachers, the results emphasize the relevance of support manifested in both formal and non-formal activity spaces, addressing various training needs. Therefore, this work departs from conceptualizations that oppose them and, instead, highlights their specificity and complementary nature in training. Thus, to sustain the professional learning and retention of novice homeroom teachers, we underscore the importance of designing formal supports tailored to their needs, as well as fostering collaborative cultures that encourage the existence of mutual support among colleagues and with specialists.